Christianity and the Origin of Sun Yat-sen’s Early Thought on Modernization - CHEN, Caijun (Journal of Research for Christianity in China (JRCC), 2025)
Sun Yat-sen completed his secondary and higher education in Hong Kong during the years from 1883 to 1892. This period, in which Sun was aged 17 to 26, represented an essential stage for his intellectual accumulation and the formation of his ideology. Sun converted to Christianity in Hong Kong due to his admiration for modern Western civilization and scientific technology. In addition, he devoted himself to studying Western learning during his university years since he knew that Christianity was the root of Western civilization. Moreover, he developed the idea of reforming the old feudal system in China by identifying himself with the Western constitutional monarchy. These are the fundamental rationales that shaped Sun’s thoughts. Instead of armed revolution, the core of Sun’s early thinking was to save the country and the people, and bring China onto the road to modernization, with specific methods of "improvement" and "innovation.